Tracing COVID-19 cluster during offline learning in the new era of pandemic - Maria Mardalena Martini Kaisar; Helen Kristin; Tria Asri Widowati; Clarissa Rachel; Anastasia Hengestu; Sem Samuel Surja; Soegianto Ali (Universitas Muhammadiyah Malang, 2024)
Since January 2022, offline learning in the COVID-19 pandemic era has been going on for nearly a year. The government is attempting to revive the education sector, including universities. Nonetheless, this policy may result in the formation of a new SARS-CoV-2 infection cluster on campuses. One of the prevention measurements is conducting COVID-19 examinations. To support this effort, the infectious disease research team at Atma Jaya Catholic University of Indonesia (AJCUI) examined COVID-19 infection by saliva specimens using RT-qPCR method, along with the completion of related questionnaire and epidemiology investigation form. Throughout the first week of December 2022, community service was conducted at the Pluit campus of AJCUI with 749 participants (98.9% students). According to RT-qPCR results, only 12 participants (1.6%) were infected with SARS-CoV-2 virus. Most participants demonstrated positive compliance with health protocols, particularly, PeduliLindungi application scanning, hand washing, and mask usage. The implementation of health protocol resulted in a low positive rate compared to North Jakarta's statistics for the same week, preventing the formation of new COVID-19 clusters. The activity effectively controlled the spread of SARS-CoV-2 in AJCUI environment, continuing the postponed 2030 agenda of the third Sustainable Development Goal to ensure good health and well-being.